Correlation between Serum Dehydroepiandrosterone Sulfate and LDL Cholesterol in Patients with Polycystic Ovarian Syndrome - Hantoro Gunawan; Irvan Ipandi; Jusak Nugraha; Ashon Sa'adi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Polycystic Ovary Syndrome (PCOS) is the most prevalent endocrine disorder in female of childbearing age. PCOS patients also have metabolic and cardiovascular disorder risks. One of the factors that can affect those disorders is androgen hormone level. Dehydroepiandrosterone, is produced by the adrenal gland, and its metabolite dehydroepiandrosterone sulphate (DHEAS) has a different effect than testosterone. DHEA and DHEAS might have a protective effect to dyslipidemia and cardiovascular disorder. LDL cholesterol is an important parameter for dyslipidemia therapy guide according to The National Cholesterol Education Program Adult Treatment Panel. The aim of this study was to analyze the correlation between DHEAS and LDL cholesterol.This research was a cross sectional observational study. DHEAS and LDL cholesterol were examined in 25 research subjects by chemiluminescent immunoassay (Immulite®, Siemens) and colorimetric enzymatic (Dimension EXL®, Siemens). These subjects were divided into 3 groups according to 2003 Rotterdam’s criteria. Spearman and Pearson’s correlation statistical analysis were done, with a significance of p-value less than 0.05This study showed a moderate negative correlation between DHEAS and LDL cholesterol (r= -0.441, p = 0.027). Group D PCOS (non-hyperandrogenic) had a strong negative correlation between DHEAS and LDL cholesterol (r=-0.717, p= 0.001). DHEA, in some literatures was shown to activate Peroxisome Proliferator Activated Response γ (PPAR γ) receptors and thereby increasing LDL-cholesterol receptors in adipose tissue and LDL-cholesterol uptake from serum. The rise in DHEAS might indicate a better prognosis for PCOS patients in terms of cardiovascular complications, especially in group D PCOS.